ANALISIS DISTRIBUSI PANGAN TERHADAP KINERJA LAYANAN MELALUI STABILISASI HARGA SEBAGAI VARIABEL MEDIASI PADA PROVINSI PAPUA BARAT DAYA - Irianto, Agus; Likewati, Wa Ode; Anwar, Vebby (POLITEKNIK LP3I JAKARTA, 2026)
Food price stability is a fundamental pillar in maintaining national food security and public purchasing power. This study aims to analyze the effect of food distribution on service performance, with price stabilization acting as a mediating variable in Southwest Papua Province. The primary issues in food distribution commonly involve extended supply chains, uneven stock allocation, and logistical disruptions, which often trigger price volatility. The analysis of relationships among variables was conducted to examine both direct and indirect effects between constructs in the research model. The model was designed to explain the role of direct and indirect distribution in influencing price stability and service performance, either directly or through a mediating mechanism. Overall, the findings indicate that the optimization of food distribution, price stability, and employee service performance constitute an integrated and interrelated system in efforts to maintain food security. The results further demonstrate that price stability plays a strategic role as a mediator in the relationship between food distribution and employee service performance. Distribution optimization oriented toward price stability provides dual benefits, namely safeguarding community welfare while enhancing the quality of public services in Southwest Papua Province.